Beneficial effects of indigenous cotton rhizobacteria on seed germinability, growth promotion and suppression of bacterial blight disease - and J.P. VERMA, K.K. MONDAL, R.P. SINGH (Indian Phytopathology, 2002)
Five, out of forty-two, cotton rhizobacteria (CRb) were selected for intensive studies on the basis of their in vitro antagonistic activity towards the most predominant and virulent race-32 of Xanthomonas axonopodis pv. malvacearum, the inducer of bacterial blight of cotton. These five isolates were identified as Pseudomonas fluorescens (CRb-26 and CRb-39), Pseudomonas putida (CRb-17) and Pseudomonas alcaligenes (CRb-9 and CRb-14). Isolate CRb-26 was most effective in inhibiting the growth of Xam.Treatment of cotton (cv. Acala 44) seeds with CRb-26 (107 cfu/ml) increased the germination of cotton (Acala-44) seeds by 12.82% and improved the development of normal seedlings by 22.58%. Application of CRb-26 on Xam inoculated seeds resulted in maximumimprovement in germination with a concomitant reduction in cotyledonary infection in comparison with the other rhizobacterial isolates tested. CRb-26 heavily colonized the cotyledons of cotton and caused a drastic reduction in Xam population. Inoculation of CRb-26 to leaves also caused a significant reduction in the disease severity.